Validity of aerobic capacity indicators derived from the progressive specific taekwondo test for prescribing sport-specific interval training - Apollaro, G.; Panascì, M.; Ouergui, I.; Franchini, E.; Ruggeri, P.; Falcó, C.; Faelli, E. (Frontiers in Physiology, 2025)
Background: The Progressive Specific Taekwondo Test (PSTT) is used to determine indicators of aerobic capacity (heart rate deflection point [HRDP] and kick frequency at the HRDP [KFDP]) useful for prescribing sport-specific training. The aim of this study was to prescribe a sport-specific interval training (IT) session at the KFDP, identified during the PSTT, and to investigate HR response and muscle power performance.